Diabetic wound healing via a co-delivery system for bone marrow derived stem cells and euphorbia hirta extract: an in vitro and in vivo study - Jiazhang Duan; Yun Yao; Jiafei Wang; Wuhua Liu; Saeed Rohani; Huagang Yang (Journal of Materials Science: Materials in Medicine)
Abstract Diabetes mellitus, a persistent metabolic disorder characterized by elevated blood glucose levels, presents a substantial global health challenge due to its escalating prevalence and associated complications. In the current study, a nanofibrous scaffold was developed for the co-delivery of bone marrow-derived stem cells and Euphorbia hirta extract into the diabetic wound beds. Scaffolds were produced using the electrospinning method, and their physicochemical and biological properties were studied in vitro. The wound healing function of the developed delivery system was investigated in a rat model of diabetic wound healing. The study showed that Euphorbia hirta extract-loaded scaffolds imparted no significant toxicity toward L929 cells and promoted their migration activity. A wound healing study showed that scaffolds loaded with both bone marrow-derived stem cells and euphorbia hirta extract had the highest wound healing activity, as shown by significantly higher wound closure percentage, collagen deposition, and epithelial thickness. Enzyme-linked immunosorbent Assay studies showed that these dressings reduced tissue oxidative stress and alleviated inflammatory responses. Graphical Abstract